AB0552 CHARACTERISTICS OF MYOSITIS SPECTRUM DISEASE - RHEUMATOID ARTHRITIS OVERLAP CASES IN A HUNGARIAN COHORT. (2nd June 2020) - Bodoki, L.; Griger, Z.; Nagy-Vincze, M.; Betteridge, Z. E.; Dankó, K.
Abstract : Background: Overlap syndromes are autoimmune disorders in which classification criteria of at least two connective tissue diseases (CTDs) are fulfilled. The Division of Clinical Immunology in Debrecen, Hungary oversees patients with idiopathic inflammatory myopathies (IIMs) since the 1980's. Objectives: In a work called The Myositis Antibody Research Project, which is coordinated together with the Bath Institute for Rheumatic Diseases (UK), authors investigated 330 patients with myositis, all treated in this Hungarian center. Methods: The aim of this retrospective study was to investigate the frequency, clinical and serological parameters and therapeutic options in myositis – rheumatoid arthritis overlap cases in this group of 330 patients. Results: The frequency of overlap cases, as seen in literature, was 13.64%. The importance of myositis-associated antibodies (MAAs) can be seen on this results: 44.44% of overlap patients, while only 7.02% of not overlap patients were MAA positive. Out of our 45 overlap patients twenty-seven myositis - RA overlap patients could be identified. Among these 27 patients the women:men ratio was 12.5:1, PM:DM ratio was 2.375:1. Muscle weakness and sceletal involvement was present in every patient, myalgia in 77.78% and Raynaud's phenomenon in 48.15% of the patients; general symptoms during disease relapse (fatigue, weight loss, fever) were present in 59.26%, 18.52% and 14.82%, respectively. Ten cases had seropositive rheumatoid arthritis, with high titer of rheumatoid factor. Authors underline the importance of lung involvement as internal organ manifestation: 8 patients had anti-synthetase antibodies (six anti-Jo-1, one anti-PL-7 and one anti-PL-12). In anti-PL-7 and anti-PL-12 positive patients interstitial lung disease (ILD) appeared some years before myositis and early agressive management of ILD resulted in fast remission of muscle weakness. Anti-Mi-2 and anti-SRP could be detected in two patients. Most frequent used disease modifying antirheumatic drugs were cyclophosphamide, methotrexate and cyclosporine, 19 patients received DMARD combination therapy. Biological therapy was used in 3 patients, intravenous or subcutaneous immuneglobulin in 4 patients and one patient with RA – myositis – antiphospholipid syndrome died because of asipartion pneumonia. Conclusion: Authors conclude that it is really challenging to treat these overlap cases: they form a very heterogenous group of patients and management has to be personalized. Disclosure of Interests: None declared